Study on the Role of NGOs in Promotion of Farmer Producer Organizations (FPOs) in Andhra Pradesh, India - Babu, T. Mahesh; Lakshmi, T.; Prasad, S. V.; Goapl, P. V. Sathya; Sumathi, V.; Murthy, B. Ramana; Kumar, T. Sravan (Cutting-edge Research in Agricultural Sciences Vol. 13, 2021)
The objective of this study is to understand the role and responsibilities of NGOs in the formation and implementation of FPOs and way forward for the success of FPOs. NGOs are more competent at facilitating farmers to learn from their own experience, they knowthe real situation at field level because they maintain closer contact with them. In Andhra Pradesh the promoting and facilitating agencies are taking joint responsibility for implementation of FPOs. NABARD, Department of Agriculture and ICRISAT etc. are working as promoting agencies, while NGOs are acting as facilitating agencies or Resource institutes for some period of time. NGOs are good at community mobilization with immense response. Local, capable and reputed NGOs having been promoted several FPOs. The role of NGO as facilitating agency is mobilization of farmers, community will, participation, help in registration of the FPO, leadership development, responsibility for management, self -governance, compliance and reports to the Government. Some of the NGOs like Rashtriya Seva Samithi (RASS), Accion Fraterna (AF-Ecology), FES, APMAS (Mahila Abhivruddhi Society, Andhra Pradesh), AAA, Centre for Sustainable Agriculture, are some of the facilitating or resource institution involved in the promotion of FPOs in Andhra Pradesh state. The NGOs are normally having social mobilizing skills, but they lack business development, supply chain and marketing skills which are critical for success of FPOs as a business entity. Hence, NGOs must have a clear exit plan for sustainable and profitable FPOs before termination of their tenure; otherwise the future of FPO might be non – futuristic.